Neuroleptic sensitivity in patients with senile dementia of Lewy body type. Issue 6855 (19th September 1992) - McKeith, I.; Fairbairn, A.; Perry, R.; Thompson, P.; Perry, E.
Abstract : OBJECTIVE--To determine the outcome of administration of neuroleptics to patients with senile dementia of Lewy body type confirmed at necropsy. DESIGN--Retrospective analysis of clinical notes blind to neuropathological diagnosis. SETTING--Specialist psychogeriatric assessment units referring cases for necropsy to a teaching hospital neuropathology service. PATIENTS--41 elderly patients with diagnosis of either Alzheimer type dementia (n = 21) or Lewy body type dementia (n = 20) confirmed at necropsy. MAIN OUTCOME MEASURES--Clinical state including extrapyramidal features before and after neuroleptic treatment and survival analysis of patients showing severe neuroleptic sensitivity compared with the remainder in the group. RESULTS--16 (80%) patients with Lewy body type dementia received neuroleptics, 13 (81%) of whom reacted adversely; in seven (54%) the reactions were severe. Survival analysis showed an increased mortality in the year after presentation to psychiatric services compared with patients with mild or no neuroleptic sensitivity (hazard ratio 2.70 (95% confidence interval 2.50-8.99); (chi 2 = 2.68, p = 0.05). By contrast, only one (7%) of 14 patients with Alzheimer type dementia given neuroleptics showed severe neuroleptic sensitivity. CONCLUSIONS--Severe, and often fatal, neuroleptic sensitivity may occur in elderly patients with confusion, dementia, or behavioural disturbance. Its occurrence may indicate senile dementia of Lewy body type and this feature has been included in clinical diagnostic criteria for this type of dementia.